Paleoenvironmental context of the Middle Stone Age record from Karungu, Lake Victoria Basin, Kenya, and its implications for human and faunal dispersals in East Africa. Issue 83 (June 2015) - Faith, J. Tyler; Tryon, Christian A.; Peppe, Daniel J.; Beverly, Emily J.; Blegen, Nick; Blumenthal, Scott; Chritz, Kendra L.; Driese, Steven G.; Patterson, David
Abstract: The opening and closing of the equatorial East African forest belt during the Quaternary is thought to have influenced the biogeographic histories of early modern humans and fauna, although precise details are scarce due to a lack of archaeological and paleontological records associated with paleoenvironmental data. With this in mind, we provide a description and paleoenvironmental reconstruction of the Late Pleistocene Middle Stone Age (MSA) artifact- and fossil-bearing sediments from Karungu, located along the shores of Lake Victoria in western Kenya. Artifacts recovered from surveys and controlled excavations are typologically MSA and include points, blades, and Levallois flakes and cores, as well as obsidian flakes similar in geochemical composition to documented sources near Lake Naivasha (250 km east). A combination of sedimentological, paleontological, and stable isotopic evidence indicates a semi-arid environment characterized by seasonal precipitation and the dominance of C4 grasslands, likely associated with a substantial reduction in Lake Victoria. The well-preserved fossil assemblage indicates that these conditions are associated with the convergence of historically allopatric ungulates from north and south of the equator, in agreement with predictions from genetic observations. Analysis of the East African MSA record reveals previously unrecognized north–south variation in assemblage composition that is consistent with episodes of population fragmentation during phases of limited dispersal potential. The grassland-associated MSA assemblages from Karungu and nearby Rusinga Island are characterized by a combination of artifact types that is more typical of northern sites. This may reflect the dispersal of behavioral repertoires—and perhaps human populations—during a paleoenvironmental phase dominated by grasslands.